INNOVATIVE METHODS IN TEACHING: THEORETICAL FOUNDATIONS AND PRACTICAL IMPLEMENTATION IN MODERN EDUCATION (American Journal of Research in Humanities and Social Sciences, 2025)
This article describes the theoretical foundations and practical application of innovative teaching methods as a fundamental aspect of modern education. The ongoing transformation in educational policies reflects a shift towards learner-centered pedagogy, emphasizing the development of creativity and personal potential among all participants in the educational process. Achieving this goal requires the diversification of educational approaches, incorporating scientifically grounded and practice-oriented innovations. This study examines how educational institutions are adapting to these changes, highlighting the necessity of flexible, research-driven methodologies in teaching and learning.